Identification of Candida species associated with vulvovaginal candidiasis by Multiplex PCR method - Mahmoudi Rad M (Tehran University Medical Journal, 2009)
"n Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:Arial; mso-bidi-theme-font:minor-bidi;} Background: Vulvovaginal candidiasis is a fungal disease with itching, and vaginal thick white discharge. Most of non-albicans species have less sensitivity to azoles. So, definition of candida species which lead to vulvovaginal candidiasis is very important to perfect usage of drugs. In the present study 191 Candida isolates from 175 patients who admitted in Gynecology department of Mahdieh Hospital during the period 1385-1387 were identified by multiplex PCR."n"nMethods: One hundred seventy five vaginal swab specimens from patients were cultured on Sabouraud Dextrose Agar (SDA). The internal transcribed spacer 1 (ITS1) region between the 18S and 5.8S rRNA genes and a specific DNA fragment within the ITS2 region of Candida albicans were amplified and the multiplex PCR products were separated by electrophoresis in 2% agarose gel (200 mA, 140V), visualized by staining with ethidium bromide, and photographed."n"nResults: One hundred ninety one Candida isolates were identified in vaginal swab specimens from 175 patients. In 89.7% of cases, single candida species and in 10.3% cases, multiple candida species were isolated. C. albicans (65.1%), C. glabrata (13.1%), C. tropicalis (6.2%), C. krusei (4%), C. guilliermondii (0.6%), C. parapsilosis (0.6%), C. glabrata and C. albicans (5.7%), C. albicans and C. parapsilosis (1.1%), C. glabrata and C. tropicalis (0.6%), C. krusei and C. tropicalis (0.6%), C. albicans and C. tropicalis (0.6%), C. krusei and C. albicans (0.6%), C. glabrata and C. krusei (0.6%), and C. glabrata and C. krusei and C. albicans (0.6%) were the cause of disease."n"nConclusion: Our findings suggest that, the common cause of both recurrent and non-recurrent vulvovaginal candidiasis was C. albicans, and then C. glabrata. Also the most common mixtures of Candida species were combination of them